Effect of moisture regulation method on viability of wild cherry seeds and determination of its threshold drought tolerance - Baharak Shiranpour; Mas'oud Tabari; Mohsen Hossini; Afsaneh Rezaee (تحقیقات جنگل و صنوبر ایران, 2012)
Regulation of seed moisture content is one of the important factors in maintaining and increasing seeds durability and quality which is made by different methods. For this reason, the trial was conducted to regulate moisture content and to determine the threshold drought resistance of wild cherry seeds, using the weight method and oven and desiccator. After calculating weight of the seed samples at the specified moisture content levels, the trend of moisture reduction in oven by temperature change and in desiccator by silica gel was investigated. The results showed that there was high correlation between the calculated moisture content by weight method and the actual one. Thus using this method for prospecting the process of desiccation in wild cherry seeds is appropriate. Also during the process of desiccation, the seed's average viability in desiccator was more than that in oven. Due to stability of the wild cherry seed's viability during the process of moisture reduction, particular threshold for drought tolerance was not defined. Therefore, certain critical moisture content for seeds of this species might not be determined.